Anti-Stokes Photoluminescence of Monolayer WS2 - Pierret, Aurelie; Tornatzky, Hans; Maultzsch, Janina (physica status solidi (b), 2019)
Anti-Stokes photoluminescence excitation of a WS2 monolayer flake between 10 and 300 K is reported herein. Even with continuous-wave lasers at low power, the emission of the exciton at excitation 100 meV below its emission energy at room temperature is observed. A mechanism which involves the trions as the intermediate state is proposed, leading to an efficient up-conversion process. In addition, it is demonstrated that phonons are the source of the additional energy needed by the system. Overall, the results provide evidence that anti-Stokes luminescence in transition metal dichalcogenides is very efficient.
CRIS-Team WoS Importer:2019-10-22